Energy efficiency of cookie residue and its effects on broiler performance - Custódio, Lidiane Rosa; Ludke, Maria do Carmo Mohaupt Marques; Santos, Ana Carolina Ferreira dos; Torres, Thaysa Rodrigues; Santos, Jussiede Silva; Barros, Julia da Silva; Ludke, Jorge Vitor; Silva, Dayane Albuquerque da; Ribeiro, Apolônio Gomes; Nascimento, Júlio Cézar dos Santos; Rabello, Carlos Bôa-Viagem; Coldebella, Arlei; et al. (Frontiers in Veterinary Science, 2025)
This study evaluated the energy value of cookie residue in broiler diets through a metabolism trial and determined the optimal inclusion level based on performance, carcass characteristics, and blood parameters. Two experiments were conducted using a completely randomized design. In the metabolism trial, 60 broilers (14 days old) were assigned to two treatments: a control diet and a diet with 30% cookie residue replacing the reference feed, with six replicates of five birds each. In the performance trial, 450 1-day-old broilers were assigned to five treatments (0%, 10%, 20%, 30%, and 40% cookie residue), with six replicates of 15 birds per treatment, evaluated at 7, 21, 35, and 42 days of age. The cookie residue showed an apparent metabolizable energy (AME) of 3,959 Kcal kg−1 and nitrogen-corrected AME (AMEn) of 3,480 Kcal kg−1. Performance results indicated that during the 1–7, 8–21, and 1–21 day periods, birds fed diets with cookie residue performed better than those on the control diet. However, no significant differences in overall performance or carcass characteristics were observed from 1 to 42 days, except for an increase in abdominal fat, a decrease in empty gizzard weight, and elevated blood cholesterol and creatinine levels—though all values remained within physiological norms. These findings suggest that cookie residue can be included in broiler diets at levels up to 40% without compromising performance or carcass quality.